Emerging Web Services Technology Volume III - Binder, Walter; Dustdar, Schahram (Whitestein Series in Software Agent Technologies and Autonomic Computing, 2010)
This third volume on Emerging Web Services Technologies follows the current - search activities in the areas of Web Services and Service Oriented Architectures. rd It includes the proceedings of the 3 Workshop on Emerging Web Services Te- th nology2008(WEWST'08),whichwascolocatedwiththe6 EuropeanConference on Web Services (ECOWS'08) and took place in November 2008 in Dublin, I- land. In addition, this volume features three papers from the ECOWS'08 business track. WEWST focuses on research contributions advancing the state of the art in Web Services technologies. The main goal of the WEWST workshop is to serve as a forum for providing early exposure and much needed feedback to grow and establish original and emerging ideas within the Web Services community. The widevarietyoftools,techniques,andtechnologicalsolutionspresentedinWEWST share one common feature - they advance the current Web Services research in new directions by introducing new, sometimes controversial ideas into the ?eld. As such, WEWST is the natural extension to the main ECOWS conference. For this edition of WEWST, we accepted 6 full papers and 3 short papers. We would like to thank the paper authors for their submissions and for their contribution to the timely preparation of these proceedings, as well as for their presentations and lively discussions during the workshop. At the same time, we would like to thank our ProgramCommittee for their work and for submitting the reviewsontime.Lastbutnotleast,wewouldliketothank theECOWSconference organizers for their help organizing a successful workshop.